2023
DOI: 10.1002/chir.23572
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation and racemization of 3‐fluorooxindoles

Abstract: Fluorinated oxindoles are frequently used building blocks in asymmetric synthesis and represent an important scaffold found in a variety of biologically relevant compounds. While it is understood that incorporation of fluorine atoms into organic molecules can improve their pharmacological properties, the impact on the configurational stability of chiral organofluorines is still underexplored. In this study, semipreparative HPLC enantioseparations of five oxindoles were carried out, and the resulting enantiomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(64 reference statements)
0
2
0
Order By: Relevance
“… 44 , 45 Based on our experience with 3-fluorooxindoles we expected that the replacement of the aryl group located at the pronucleophilic carbon center by fluoride would largely alter its reactivity. 46 Indeed, we found that the squaramide protocol does not give any product when 3-fluorooxindoles are employed, which highlights the strikingly different reactivity of organofluorines compared to their nonfluorinated analogs and the necessity to develop new catalytic methods that address this ( Table 1 , entry 1). We therefore initiated the search for suitable conditions with the comprehensive screening of organocatalysts, oxindole protecting groups, solvents, and base additives and by varying the reaction temperature (see Table 1 and SI ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“… 44 , 45 Based on our experience with 3-fluorooxindoles we expected that the replacement of the aryl group located at the pronucleophilic carbon center by fluoride would largely alter its reactivity. 46 Indeed, we found that the squaramide protocol does not give any product when 3-fluorooxindoles are employed, which highlights the strikingly different reactivity of organofluorines compared to their nonfluorinated analogs and the necessity to develop new catalytic methods that address this ( Table 1 , entry 1). We therefore initiated the search for suitable conditions with the comprehensive screening of organocatalysts, oxindole protecting groups, solvents, and base additives and by varying the reaction temperature (see Table 1 and SI ).…”
Section: Resultsmentioning
confidence: 96%
“…To date, several groups have investigated stereoselective carbon–carbon bond formation with indoles, isatins, or oxindole derivatives, and quinone methides as Michael acceptors, giving access to important chiral diarylmethines. Asymmetric conjugate additions of 3-aryloxindoles to quinone methides have been reported by Enders and Fan using squaramide catalysts. , Based on our experience with 3-fluorooxindoles we expected that the replacement of the aryl group located at the pronucleophilic carbon center by fluoride would largely alter its reactivity . Indeed, we found that the squaramide protocol does not give any product when 3-fluorooxindoles are employed, which highlights the strikingly different reactivity of organofluorines compared to their nonfluorinated analogs and the necessity to develop new catalytic methods that address this (Table , entry 1).…”
Section: Resultsmentioning
confidence: 99%